Socio-Economic Factors Influencing HIV/AIDS Infections in the South African Youth - Gaston, Rugiranka Tony; Ramroop, Shaun; Habyarimana, Faustin (Universitas Syiah Kuala, 2025)
Objective The HIV/AIDS is one of the diseases that is prevalent on the African continent and in southern African regions, particularly. South Africa is known as a country with socio-economic challenges that possibly contribute to the high rate of people living with HIV/AIDS experienced by the country. The objective of the current study is to investigate the effect of selected socio-economic factors on HIV infections among South African youth aged between 15 and 25 years old.Design/Methodology To achieve the study objective, the autoregressive distributed lag (ARDL) approach, bounds testing techniques, and error correction model were applied on the data sample spanning from 1980 to 2023.Results The findings indicate that, in the long-run, all selected explanatory variables have a significant effect on youth newly infected with HIV. However, in the short-run, only the lagged number of infected people and economic growth were found to have a significant impact on youth newly infected.Research limitations/implications Based on the results, it is imperative to improve financial conditions and create more job opportunities to reduce the number of youths newly infected with HIV owing to their penurious conditions.Novelty/Originality The distinction between short-run and long-run effects of socio-economic factors on HIV infections. This research highlights the critical role of economic conditions and job opportunities in reducing new HIV infections among young people.